PEMBENTUKAN KARAKTER BIJAKSANA, WIBAWA DAN TANGGUNG JAWAB MELALUI PERTUNJUKAN TARI TOPENG TUMENGGUNG - Nasywa Raudhatul Jannah; Aim Abdulkarim; Rahmat Rahmat (CV. ADIBA AISHA AMIRA, 2025)
The decline in leadership traits such as wisdom, authority, and responsibility has become a critical issue in modern society, especially amidst the rise of bullying, weak character education, and the lack of exemplary leadership figures. This study explores the Topeng Tumenggung dance performance as an educational and transformational medium for cultivating noble leadership values. More than mere entertainment, the Topeng Tumenggung dance is a symbolic representation of ethical and moral values embedded in the local culture of Indramayu. Using a descriptive qualitative approach, data were collected through observation, interviews, literature review, and documentation at the Mimi Rasinah dance studio. The findings reveal that the character of Tumenggung—rich in attributes of dignity, wisdom, and responsibility—is effectively conveyed through expressive movements, mask usage, and performance narratives. This traditional dance has proven to positively influence character development among both performers and audiences, particularly the younger generation. Therefore, traditional performing arts such as Topeng Tumenggung possess great potential as alternative strategies for character education, grounded in local culture and capable of deeply engaging the affective dimension.